Intra-Abdominal and Abdominal Wall Desmoid Fibromatosis. Issue 1 (June 2016) - Howard, J.; Pollock, Raphael
Abstract Desmoid fibromatosis is a rare but locally aggressive tumor comprised of myofibroblasts. Desmoids do not have the ability to metastasize but can cause significant morbidity and mortality by local invasion. These tumors may occur throughout the body, but are commonly found on the abdominal wall and within the intestinal mesentery. Desmoids in these areas may cause unique clinical problems for physicians and patients. Mutations in either the β-catenin or theAPC genes are usually the cause for the development of these tumors with the former comprising the sporadic development of tumors and the latter being associated with familial adenomatous polyposis syndrome. Surgical resection with histologically negative margins has been the cornerstone of therapy for this disease, but this paradigm has begun to shift. It is now common to accept a microscopically positive margin after resection as recurrence rates may not be significantly affected. An even more radical evolution in management has been the recent movement towards "watchful waiting" when new desmoids are diagnosed. As the natural history of desmoids has become better understood, it is evident that some tumors will not grow and may even spontaneously regress sparing patients the morbidity of more aggressive therapy. Other modalities of treatment for desmoids include radiation and systemic therapy which both can be used adjuvantly or as definitive therapy and have shown durable response rates as single therapy regimens. The decision to use radiation and/or systemic therapies is often based on tumor biology, tumor location, surgical morbidity, and patient preference. Systemic therapy options have increased to include hormonal therapies, non-steroidal anti-inflammatory drugs and chemotherapy, as well as targeted therapies. Unfortunately, the rarity of this disease has resulted in a scarcity of randomized trials to evaluate any of these therapies emphasizing the need for this disease to be treated at high volume multidisciplinary institutions.